EDUCAÇÃO E RELIGIÃO NA PRELAZIA DO MARAJÓ: um estudo sobre a Ordem dos Agostinianos Recoletos e a criação de escola em Breves-PA - CUSTÓDIO, Luciane Barbosa (2024)
This study presents the relationship between education and religion in the Prelature of Marajó as its theme. This theme is discussed based on a school for early childhood education and elementary education created by the Order of Augustinian Recollects (OAR) in Breves-PA. The problem is anchored in the following questions: What relationship is there between the Catholic religion and the education developed by the OAR school in Breves-PA? How does the Order of Augustinian Recollects contribute to school education in Breves-PA? Is there an influence of this Order on the concept of school, education and curriculum? The objective of this investigation is to understand the relationship established between the Catholic religion and the education carried out in the school space belonging to OAR in Breves. In a specific way, we sought to know the contributions of OAR to school education in Breves and to identify the possible influences of this Order in the conception of education, school and curriculum. This is an exploratory research with a qualitative approach that used bibliographic research, document analysis and field research as a methodological procedure. To collect the data in the field, we used the semi-structured interview. The analysis of the empirical data followed the assumptions of the content analysis technique, in particular the elaboration of categories and inferences. In this process of the bibliographic base, the following categories emerged: cultural plurality; secular teaching and religious freedom. From the empirical data, we selected as categories: the role of OAR in Breves; school to train and also socialize aspects of the Catholic religion; curriculum. The results obtained show that school education and religion with a focus on Catholicism are intertwined. However, there is no religious imposition on the educational background of children, not least because many children belong to non-Catholic families. The influence of OAR in the conceptions of education, school and curriculum does not occur directly, it can be said that it occurs indirectly and through the Catholic guidance rituals adopted in the reception of children and in activities such as the “Coronation of Our Lady”. It is concluded that the training offered at the school managed by OAR corroborates for all existing religious denominations to be recognized, we can say that there is no room for indoctrination, exclusivity, segregation or religious intolerance, being able to serve all religious groups. In this sense, we see the opportunity for a dialogue that brings together and enables communication and respect between religions.